Sfp-type PPTase inactivation promotes bacterial biofilm formation and ability to enhance wheat drought tolerance - Timmusk, Salme; Kim, Seong-Bin; Nevo, Eviatar; Abd El Daim, Islam; Ek, Bo; Bergquist, Jonas; Behers, Lawrence (Frontiers in Microbiology, 2015)
Paenibacillus polymyxa is a common soil bacterium with broad range of practical applications. An important group of secondary metabolites in P. polymyxa are non-ribosomal peptide and polyketide derived metabolites (NRPs/PKs). Modular non-ribosomal peptide synthetases catalyze main steps in the biosynthesis of the complex secondary metabolites. Here we report on the inactivation of an A26 Sfp-type 4'-phosphopantetheinyl transferase (Sfp-type PPTase). The inactivation of the gene resulted in loss of NRPs/PKs production. In contrast to the former Bacillus spp. model the mutant strain compared to wild type showed greatly enhanced biofilm formation ability. A26Δsfp biofilm promotion is directly mediated by NRPs/PKs, as exogenous addition of the wild type metabolite extracts restores its biofilm formation level. Wheat inoculation with bacteria that had lost their Sfp-type PPTase gene resulted in two times higher plant survival and about three times increased biomass under severe drought stress compared to wild type. Challenges with P. polymyxa genetic manipulation are discussed.